Wealth-based equity in maternal, neonatal, and child health services utilization: a cross-sectional study from Ethiopia - Alem Desta Wuneh; Araya Abrha Medhanyie; Afework Mulugeta Bezabih; Lars Åke Persson; Joanna Schellenberg; Yemisrach Behailu Okwaraji (BMC, 2019)
Abstract Background Despite the pro-poor health policies in Ethiopia, the utilization of maternal, neonatal, and child health services remains a challenge for the country. Health equity became central in the post-2015 Sustainable Development Goals globally and is a priority for Ethiopia. The aim of this study was to assess equity in utilization of a range of maternal and child health services by applying absolute and relative equity indices. Methods Data on maternal and child health utilization emanated from a baseline survey conducted for a large project 'Optimizing the Health Extension Program from December 2016 to February 2017 in four regions of Ethiopia. The utilization of four or more antenatal care visits; skilled birth attendance; postnatal care within 2 days after childbirth; immunization with BCG, polio 3, pentavalent 3, measles and full immunization of children aged 12-23 months; and vitamin A supplementation for 6-23 months old children were stratified by wealth quintiles. The socioeconomic status of the household was assessed by household assets and measured by constructing a wealth index using principal component analysis. Equity was assessed by applying two absolute inequity indices (Wealth index [quintile 5- quintile 1] and slope index of inequality) and two relative inequity indices (Wealth index [quintile5: quintile1] and concentration index). Results The maternal health services utilization was low and inequitably distributed favoring the better-off women. About 44, 71, and 18% of women from the better-off households had four or more antenatal visits, utilized skilled birth attendance and postnatal care within two days compared to 20, 29, and 8% of women from the poorest households, respectively. Skilled birth attendance was the most inequitably distributed maternal health service. All basic immunizations: BCG, polio 3, pentavalent 3, measles, and full immunization in children aged 12-23 months and vitamin A supplementation were equitably distributed. Conclusion Utilization of maternal health services was low, inequitable, and skewed against women from the poorest households. In contrast, preventive child health services were equitably distributed. Efforts to increase utilization and reinforcement of pro-poor and pro-rural strategies for maternal, newborn and immunization services in Ethiopia should be strengthened.